Can a continuous quality improvement program create culturally safe emergency departments for Aboriginal people in Australia? A multiple baseline study - Thomas Gadsden; Gai Wilson; James Totterdell; John Willis; Ashima Gupta; Alwin Chong; Angela Clarke; Michelle Winters; Kym Donahue; Sonia Posenelli; Louise Maher; Jessica Stewart; et al. (BMC, 2019)
Abstract Background Providing culturally safe health care can contribute to improved health among Aboriginal people. However, little is known about how to make hospitals culturally safe for Aboriginal people. This study assessed the impact of an emergency department (ED)-based continuous quality improvement program on: the accuracy of recording of Aboriginal status in ED information systems; incomplete ED visits among Aboriginal patients; and the cultural appropriateness of ED systems and environments. Methods Between 2012 and 2014, the Aboriginal Identification in Hospitals Quality Improvement Program (AIHQIP) was implemented in eight EDs in NSW, Australia. A multiple baseline design and analysis of linked administrative data were used to assess program impact on the proportion of Aboriginal patients correctly identified as Aboriginal in ED information systems and incomplete ED visits in Aboriginal patients. Key informant interviews and document review were used to explore organisational changes. Results In all EDs combined, the AIHQIP was not associated with a reduction in incomplete ED visits in Aboriginal people, nor did it influence the proportion of ED visits made by Aboriginal people that had an accurate recording of Aboriginal status. However, in two EDs it was associated with an increase in the trend of accurate recording of Aboriginality from baseline to the intervention period (odds ratio (OR) 1.31, p < 0.001 in ED 4 and OR 1.15, p = 0.020 in ED 5). In other words, the accuracy of recording of Aboriginality increased from 61.4 to 70% in ED 4 and from 72.6 to 73.9% in ED 5. If the program were not implemented, only a marginal increase would have occurred in ED 4 (from 61.4 to 64%) and, in ED 5, the accuracy of reporting would have decreased (from 72.6 to 71.1%). Organisational changes were achieved across EDs, including modifications to waiting areas and improved processes for identifying Aboriginal patients and managing incomplete visits. Conclusions The AIHQIP did not have an overall effect on the accuracy of recording of Aboriginal status or on levels of incomplete ED visits in Aboriginal patients. However, important organisational changes were achieved. Further research investigating the effectiveness of interventions to improve Aboriginal cultural safety is warranted.